2014
DOI: 10.1016/j.celrep.2014.10.054
|View full text |Cite
|
Sign up to set email alerts
|

MOV10 and FMRP Regulate AGO2 Association with MicroRNA Recognition Elements

Abstract: The fragile X mental retardation protein FMRP regulates translation of its bound mRNAs through incompletely defined mechanisms. FMRP has been linked to the microRNA pathway and we show here that it associates with the RNA helicase MOV10, also associated with the microRNA pathway. FMRP associates with MOV10 directly and in an RNA-dependent manner and facilitates MOV10-association with RNAs in brain and cells suggesting a cooperative interaction. We identified the RNAs recognized by MOV10 using RNA-IP and iCLIP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(133 citation statements)
references
References 66 publications
3
127
3
Order By: Relevance
“…Thus, this role of FMRP is unlikely to explain the widespread epigenetic misregulation we observed. Finally, while we observed changes in KO genes expression by RNA-sequencing, these data do not distinguish between changes in transcription and changes on transcript stability which may result from possible interactions between FMRP and Argonaute (Caudy et al, 2002; Jin et al, 2004; Kenny et al, 2014). However, given the correlation between gene expression changes and changes in histone modifications at those genes, as well as the ability of JQ1 to reverse changes in transcript expression, chromatin regulation is likely a key player in these alterations.…”
Section: Discussioncontrasting
confidence: 78%
“…Thus, this role of FMRP is unlikely to explain the widespread epigenetic misregulation we observed. Finally, while we observed changes in KO genes expression by RNA-sequencing, these data do not distinguish between changes in transcription and changes on transcript stability which may result from possible interactions between FMRP and Argonaute (Caudy et al, 2002; Jin et al, 2004; Kenny et al, 2014). However, given the correlation between gene expression changes and changes in histone modifications at those genes, as well as the ability of JQ1 to reverse changes in transcript expression, chromatin regulation is likely a key player in these alterations.…”
Section: Discussioncontrasting
confidence: 78%
“…To our knowledge, FMRP activates the translations of at least four other mRNAs including superoxide dismutase 1 (Sod1), achaetescute homolog-1 (ASH1), Kv4.2, and nitric oxide synthase 1 (NOS1) [17,[51][52][53]. We speculate that the dual-function of FMRP in controlling translation could at least be partially resulted from the specific binding sites of target mRNAs, since the interaction between FMRP and those binding sites can change the conformation of target mRNAs or the configuration of other bound proteins, and thus result in activation or suppression of translation [17,52,54]. Several studies have evidenced that FMRP dephosphorylation can turn off the suppression of polysomes using qPCR.…”
Section: Discussionmentioning
confidence: 97%
“…MOV10 is a multifunctional protein involved in many cellular biological processes. It has been reported that MOV10 facilitates the assembly and maturation of the microRNA-inducing silencing complex (miRISC) and functions in UPF1-mediated mRNA degradation (31,46,47). In addition, MOV10 was reported to affect the replication of several kinds of viruses, including HIV-1, hepatitis C virus (HCV), and hepatitis B virus (HBV) (48-50, 63, 64).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, RNA helicases are RNA-binding proteins involved in the regulation of RNA transcription, mRNA translocation, and RNA decay (44,45). MOV10 had been reported to participate in the replication of various RNA viruses, in the RNAi pathway, and in mRNA decay (31,(46)(47)(48)(49)(50). Based on the important role of MOV10 in RNA processing and antiviral function, we were therefore interested in its potential role in the life cycle of IAV.…”
Section: Isolation Of Influenza a Virus Vrnp Complex And Identificatimentioning
confidence: 99%